2018
DOI: 10.1080/23322039.2018.1510718
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of economic growth in Hong Kong: The role of stock market development

Abstract: We assessed the impact of stock market development on growth in Hong Kong for the period 1986Q2 to 2015Q4. By constructing a composite index of stock market development and controlling for the key determinants of growth, we found stock market development to promote growth both in the short and long run. We further constructed an alternative index of stock market development and found this conclusion to be robust. Our findings are broadly consistent with the growth experience of Hong Kong. Policies meant to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In the long term, the In this study, on the aspect of macro indicators in the long term, the resulting model tends to be consistent with previous studies. Stock market prices are still considered capable of predicting and encouraging economic growth (Osaseri & Osamwonyi, 2019;Cave et al, 2020;Ho, 2018). In the case of exchange rates, the study is in line with the results of the studyChan et al, (2019) that in the long term the strengthening of the domestic currency exchange rate or undervaluation will encourage the economy, because this will trigger export activities and trigger production activities so as to increase production output.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the long term, the In this study, on the aspect of macro indicators in the long term, the resulting model tends to be consistent with previous studies. Stock market prices are still considered capable of predicting and encouraging economic growth (Osaseri & Osamwonyi, 2019;Cave et al, 2020;Ho, 2018). In the case of exchange rates, the study is in line with the results of the studyChan et al, (2019) that in the long term the strengthening of the domestic currency exchange rate or undervaluation will encourage the economy, because this will trigger export activities and trigger production activities so as to increase production output.…”
Section: Discussionsupporting
confidence: 80%
“…The policy held by the central bank of a country is the key in regulating economic stability which will also have an impact on the real condition of a country's economy (Muhammad et al, 2017). In several theories, such as that revealed by Chouwdury (2005) that the financial aspect (monetary) with real economic conditions in Previous researchers have done a lot of analysis and concept development on how data macroeconomic factors become a forecasting medium in regulating the growth and stability of a country's economy, such as examining the relationship and relationship between the capital market or stock market and economic growth (Cave et al, 2020;Coşkun et al, 2017;Ho, 2018;Muharam et al, 2019;Nathaniel et al, 2020;Nguyen & Bui, 2019;Oprea & Stoica, 2018;Osaseri & Osamwonyi, 2019 ;Pradhan, 2018), inflation and economic growth (Abuoliem et al, 2019;Agbonlahor, 2014;Balk et al, 2020;Bayuni & Srisusilawati, 2018;Denbel et al, 2016;Fountas et al, 2002;Oliinyk et al, 2020;A. Uddin et al, 2019;Ullah et al, 2020), as well as currency exchange rates and economic growth (Babubudjnauth, 2020;Chan et al, 2019;Feriyantoa, 2020;Mlambo, 2020;Oliinyk et al, 2020;Park, Ryu, & Lee, 2019).…”
Section: Figure 1 World Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings, however, remain contradictory across different countries and different periods. Several studies reported a positive relationship in the short-and long-run between stock market and growth for the countries where the stock markets are well-established such as Canada, Finland, France, Germany, Australia, Hong Kong, Singapore, Thailand, and Malaysia (for examples, see Arestis, Chortareas, and Magkonis (2015), Cojocaru, Falaris, Hoffman, and Miller (2016), Durusu-Ciftci, Ispir, and Yetkiner (2017), Pradhan, Arvin, Bahmani, Hall, and Norman (2017), Hoque and Yakob (2017), Ho (2018), andSamsi, Cheok, andYusof (2019)). Meanwhile, many studies investigated nonlinearities and showed negative results for the countries where the financial sectors are dominated by banks or the stock markets are relatively young such as Ecuador, Jordan, Peru, Saudi Arabia, Nigeria and Bangladesh (for examples, see Mishra and Narayan (2015), Sahay, Čihák, N'Diaye, and Barajas (2015), Samargandi, Fidrmuc, and Ghosh (2015), Prettner (2016), Owusu (2016), Banerjee, Ahmed, and Hossain (2017), Prochniak andWasiak (2017), andRehman (2018)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Prats and Sandoval (2020) (Prats & Sandoval, 2020), there is evidence that GDP and stock market value are causally related in both directions. Ho (2018) suggests that the stock market promotes growth in both the long and short term.…”
Section: Background Of Studymentioning
confidence: 99%